PERFORMANCE ANALYSIS OF A SIMPLE ALUMINIUM STRUCTURE IN FIRE CONDITIONS (Advances in Civil and Architectural Engineering, 2022)
In this study, a performance analysis of a simple aluminum (EN AW-6061 T6) structure is presented under fire conditions. A simple structure was also analyzed in a steel (S235) building variant for comparison purposes. All loads were determined in accordance with Eurocode rules. Internal forces were calculated using the SCIA Engineer 19.1. Cross-section resistances and element stability checks were performed using EN1993-1-1 and EN1993-1-2 for steel and EN1999-1-1 and EN1999-1-2 for aluminum. The main conclusion of this study is that aluminum, although initially more expensive than steel, can offer rational solutions for structures in which the difference in structural performance in fire conditions between aluminum and steel is not sufficiently drastic to yield significantly higher costs for fire protection in aluminum. Furthermore, aluminum building variants offer less mass, easier transport, and resistance to corrosion. Hence, for structures with the aforementioned factors as the main demands, aluminum can be a better option than steel.